Rasio Netrofil Limfosit dan Limfositopenia Sebagai Penanda Sepsis - Puja Laksana Maqbul; Ery Leksana; Muhammad Sofyan Harahap (Medica Hospitalia : Journal of Clinical Medicine, 2019)
Background: The state of sepsis will initially lead to an increase in the number of neutrophils followed by an increase in lymphocytes, a state of sepsis that last longer will cause apoptosis of lymphocytes, so that the neutrophil lymphocyte ratio will increase, and absolute limfositopenia will occur which can be used as an indicator of sepsis. Aim: Knowing the value of RNL and lymphocyte count in patients suspected of sepsis in the ICU Dr. Kariadi Hospital Semarang Methods: This study is a non-experimental diagnostic and cross sectional design with a sample of 30 patients. Blood samples were taken from ICU patients with two or more signs of SIRS and suspected infection for leukocyte count and blood culture examination, then the data were analyzed using ROC curves. Result: The source of infection occurred in the digestive tract (43.3%), obstetrics gynecology (23.3%), respiratory tract (16.7%), cerebrovascular (10%) and urinary tract (6.7%). Neutrophils Lymphocytes count ratio has AUC 0,425 (sensitivity 60% and specificity 20%), absolute Limfositopenia has AUC 0,425 (sensitivity 40% and specificity 40%), while the RNL and Limfositopenia has AUC 0.575 (sensitivity 70% and specificity 45%). Conclusion: Neutrophils Lymphocytes count ratio and absolute Lymphocytopenia can not be used as an indicator of sepsis in ICU’s patients despite having a sensitivity of 70% and specifity 45%. Keywords: Sepsis, Ratio Neutrophils Lymphocytes, Limfositopenia absolute. Latar Belakang: Keadaan sepsis pada awalnya akan menyebabkan peningkatan jumlah netrofil diikuti oleh peningkatan limfosit, keadaan sepsis yang bertahan akan menyebabkan apoptosis dari limfosit, sehingga rasio netrofil limfosit akan meningkat, dan terjadi limfositopenia yang dapat dijadikan indikator sepsis. Tujuan: Mengetahui nilai RNL dan hitung limfosit pada pasien dicurigai sepsis di RSUP Dr. Kariadi Semarang Metode: Penelitian ini merupakan penelitian diagnostik non eksperimental dengan desain cross sectional dengan jumlah sampel 30 pasien. Pasien ICU dengan dua atau lebih tanda SIRS dan dicurigai infeksi diambil sampel darah untuk dilakukan pemeriksaan hitung jenis leukosit dan pemeriksaan kultur darah, kemudian data dianalisis menggunakan kurva ROC. Hasil: Sumber infeksi terbanyak terjadi pada traktus digestivus (43,3%), obstetri ginekologi (23,3%), traktus respiratorius (16,7%), cerebrovaskular (10%) dan traktus urinarius (6,7%). Rasio Netrofil Limfosit memiliki AUC 0,425 (sensitivitas 60% dan spesifitas 20%), Limfositopenia absolut memiliki AUC 0,425 (sensitivitas 40% dan spesifitas 40%), sedangkan RNL dan Limfositopenia memiliki AUC 0,575 (sensitivitas 70% dan spesifitas 45%). Kesimpulan: Rasio Netrofil Limfosit dan Limfositopenia absolut tidak bisa dijadikan indikator sepsis pada pasien-pasien di ICU walaupun memiliki sensitivitas 70% dan spesisifitas 45%. Kata kunci: Sepsis, Rasio Netrofil Limfosit, Limfositopenia absolut